Superhelical DNA as a preferential binding target of 14-3-3γ protein - Brázda, Václav; Cechová, Jana; Coufal, Jan; Rumpel, Sigrun; Jagelská, Eva B (Journal of biomolecular structure & dynamics, 2012)
The 14-3-3 protein family is a highly conserved and widely distributed group of proteins consisting of multiple isoforms in eukaryotes. Ubiquitously expressed, 14-3-3 proteins play key roles in DNA replication, cell cycle regulation, and apoptosis. The function of 14-3-3 proteins is mediated by interaction with a large number of other proteins and with DNA. It has been demonstrated that 14-3-3γ protein binds strongly to cruciform structures and is crucial for initiating replication. In this study, we analyzed DNA binding properties of the 14-3-3γ isoform to linear and supercoiled DNA. We demonstrate that 14-3-3γ protein binds strongly to long DNA targets, as evidenced by electrophoretic mobility shift assay on agarose gels. Binding of 14-3-3γ to DNA target results in the appearance of blurry, retarded DNA bands. Competition experiments with linear and supercoiled DNA on magnetic beads show very strong preference for supercoiled DNA. We also show by confocal microscopy that 14-3-3 protein in the HCT-116 cell line is co-localized with DNA cruciforms. This implies a role for the 14-3-3γ protein in its binding to local DNA structures which are stabilized by DNA supercoiling.
Keywords: HCT116 buňky; Humans; Recombinant Fusion Proteins; Protein Binding; klonování DNA; Electrophoretic Mobility Shift Assay; Escherichia coli; vazebná místa; lidé; plazmidy; Binding Sites; proteiny 14-3-3; retardační test; DNA Replication; superhelikální DNA; replikace DNA; kompetitivní vazba; 14-3-3 Proteins; rekombinantní fúzní proteiny; vazba proteinů; Binding, Competitive; HCT116 Cells; Cloning, Molecular; křížová struktura DNA; DNA, Superhelical; Plasmids; DNA, Cruciform